2015
DOI: 10.1515/math-2015-0078
|View full text |Cite
|
Sign up to set email alerts
|

Duplication in a model of rock fracture with fractional derivative without singular kernel

Abstract: : We provide a mathematical analysis of a break-up model with the newly developed Caputo-Fabrizio fractional order derivative with no singular kernel, modeling rock fracture in the ecosystem. Recall that rock fractures play an important role in ecological and geological events, such as groundwater contamination, earthquakes and volcanic eruptions. Hence, in the theory of rock division, especially in eco-geology, open problems like phenomenon of shattering, which remains partially unexplained by classical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…However, there were some serious issues that were pointed out against this new finding. First the kernel used was not non-local; second the anti-derivative associated is just the average of the function and its integral [1,2,4,[8][9][10][11]. Therefore it was concluded that, the operator was rather a filter than a fractional derivative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were some serious issues that were pointed out against this new finding. First the kernel used was not non-local; second the anti-derivative associated is just the average of the function and its integral [1,2,4,[8][9][10][11]. Therefore it was concluded that, the operator was rather a filter than a fractional derivative.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it was concluded that, the operator was rather a filter than a fractional derivative. However we should point out that many works were done around this new finding with great success [1,2,4,10,11]. This derivative was used in mechanical engineering, in groundwater studies, in thermal science, in diffusion model and other [1,2,4,10].…”
Section: Introductionmentioning
confidence: 99%
“…We used the local derivative in one model, the Caputo derivative with power function kernel with singularity and the Caputo-Fabrizio derivative with exponential kernel, which has no singularity [21][22][23][24]. We presented the existence and uniqueness of the model with local derivative and then we derived approximate solutions via iterative method.…”
Section: Discussionmentioning
confidence: 99%
“…Jafari et al [24] applied the HAM in order to solve the high orderly fractional differential equation analyzed by Diethelmand and Ford [25]. In [26], is produced a mathematical analysis of an example studied the Caputo-Fabrizio fractional derivative, where analytical and calculation advances are fined. Morales-Delgado et al [27] presented LHAM to supply new solutions in case of every two fractional operators.…”
Section: Introductionmentioning
confidence: 99%